Role of pharmacist in the management of Hansen's Disease: A scoping review - Elza Cristina de Oliveira Duarte; Nathania Rodrigues Santiago; Marília Berlofa Visacri; Tácio de Mendonça Lima (Elsevier, 2023)
Background: Stakeholders and healthcare professionals have an essential role in the elimination of Hansen's Disease. Of these, pharmacists provide core services that assist the management of these patients with the supply of medicines and clinical actions. Objectives: To summarize evidence on the role of pharmacist in the management of Hansen's Disease. Methods: A literature search was performed in MEDLINE, Embase, Scopus, Web of Sciences, LILACS, and Google Scholar for studies published until September 29th, 2022 without language restriction. Studies that reported actions provided by pharmacists in the management of patients with Hansen's Disease were included. The pharmacist interventions identified in the studies were described based on key domains in DEPICT v.2. Two independent reviewers performed study selection and data extraction and any disagreements were resolved by third and fourth authors. Results: A total of 751 records were identified, of which 8 studies fully met the eligibility criteria. Most of them were conducted in Brazil (n = 5), in an ambulatory setting (n = 8) and the most common study design was descriptive cross-sectional (n = 6). Different roles of pharmacists were identified, such as medication review, therapeutic drug monitoring, patient education, drug information, and dispensing. All studies described pharmacist interventions for patients through one-on-one contact and face-to-face. Pharmacists were responsible for patient counseling (n = 8), suggestions for change in therapy (n = 2), and monitoring results report (n = 2). The studies reported benefits associated with pharmacist interventions, despite the limited descriptions regarding these actions. Conclusions: Few studies that described the activities of pharmacists in the management of Hansen's Disease were found. As the studies did not offer a satisfactory level of description and quality, further research should be conducted to strengthen this field.